Joint European development strategy - Erich Ehm (Intereconomics, 1971)
On July 27,1971, the Commission of the European Communities has submitted a memorandum on a Joint European development policy to the governments of the EEC's member states. It has thereby called for a beginning of the discussion on cooperative action by the Communities also in the field of development policies.
Keywords: 330; Development Policy